Level of Experience Does Not Influence the Accuracy of Radiographic and Ultrasound Measurements of Magnetically Controlled Growing Rod Distractions. Issue 5 (May 2020) - Bye, Brian; Graham, Chelsea K.; Robbins, Christopher; Wallace, Nicholas; Lindsey, Benjamin; Caird, Michelle S.; Farley, Frances A.; Li, Ying
Abstract : Background: Magnetically controlled growing rods (MCGR) have become a popular surgical option for the treatment of early-onset scoliosis. Both radiographs and ultrasound are currently used to measure the amount of length achieved when MCGRs are distracted. Previous studies have investigated the intraobserver and interobserver reliability of radiographic and ultrasound measurements of MCGR distraction. Some authors have reported that there is a "learning curve" in measuring MCGR lengthening with ultrasound, suggesting that new users require several months of experience before they can accurately perform the measurements. The goal of this study was to determine whether surgical experience of the rater is associated with the accuracy of radiographic and ultrasound measurements of MCGR distraction. Methods: Six raters evaluated 29 deidentified radiographs and 30 ultrasound images from early-onset scoliosis patients with MCGR. Raters had varying levels of experience, ranging from a senior fellowship-trained pediatric orthopaedic surgeon to a junior orthopaedic surgery resident. Raters measured the amount of rod distraction in 2 sessions spaced 2 weeks apart. All raters were provided with a document demonstrating the radiographic and ultrasound measurement techniques before the first round of measurements. Intraclass correlation coefficients were calculated. Results: Excellent intraobserver and interobserver agreement was achieved for both radiographic and ultrasound measurements of MCGR distraction. Subanalysis based on experience level showed that excellent intraobserver agreement was maintained with no evidence of decreased reliability in raters with less experience. Conclusions: Excellent intraobserver and interobserver agreement was obtained with radiographic and ultrasound measurements of MCGR distraction, regardless of the experience level of the rater. Posting a document with the radiographic and ultrasound measurement techniques in the orthopaedic surgery clinic, and perhaps also the radiology reading room may help avoid inaccurate measurements of distraction length secondary to a learning curve. Level of Evidence: Level III—diagnostic. Abstract : Supplemental Digital Content is available in the text.